1981
DOI: 10.1080/00362178185380481
|View full text |Cite
|
Sign up to set email alerts
|

Survival ofParacoccidioides brasiliensisyeast cells under microaerophilic conditions

Abstract: The ability of P. brasiliensis yeast cells to withstand microaerophilic-conditions was investigated in a liquid medium distributed in tall columns in screw-capped tubes. Young cells of three isolates were inoculated on top of the medium, and the tubes were incubated aerobically and anaerobically at 36 °C for 28 days. The viability of cells that had sedimented to the bottoms of the tubes was studied by fluorescent micro.~6opy and by their capacity to resume growth when transferred to fresh medium undercontinuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The yeast and mycelial phases of P. brasiliensis both require a generous supply of oxygen for growth (258); however, young yeast cells can adapt gradually to reduced oxygen tension and enter a resting stage. Resting cells can regain metabolic activity when placed under adequate conditions of oxygenation (258). This capacity may well explain the prolonged latency of this mycosis (4).…”
Section: Figmentioning
confidence: 99%
“…The yeast and mycelial phases of P. brasiliensis both require a generous supply of oxygen for growth (258); however, young yeast cells can adapt gradually to reduced oxygen tension and enter a resting stage. Resting cells can regain metabolic activity when placed under adequate conditions of oxygenation (258). This capacity may well explain the prolonged latency of this mycosis (4).…”
Section: Figmentioning
confidence: 99%
“…However, Pedroso found that the semianaerobic environment offered by liquid cultures in tall columns was advantageous for the primary isolation of the yeast phase [5]. The latter report, however, is not very detailed, thus hindering complete assessment of the finding.Recent experimental studies revealed that the yeast-like cells of this fungus can accommodate to the microaerophilic conditions present in stationary liquid cultures [9]. Long periods of latency are known to occur in human paracoccidioidomycosis [2] and we therefore wondered whether dormancy of P. brasiliensis, similar to that seen in vitro, might occur in vivo.…”
mentioning
confidence: 99%
“…Recent experimental studies revealed that the yeast-like cells of this fungus can accommodate to the microaerophilic conditions present in stationary liquid cultures [9]. Long periods of latency are known to occur in human paracoccidioidomycosis [2] and we therefore wondered whether dormancy of P. brasiliensis, similar to that seen in vitro, might occur in vivo.…”
mentioning
confidence: 99%